Handicrafts, philanthropy and self-help: the Fort Napier Kamp-Industrie during World War I - Dominy, G.; Reusch, D. (Southern African Humanities, 2021)
The establishment and development of an organised craft industry by the German and Austro-Hungarian internees at Fort Napier during the First World War was one of the most important aspects of their experiences in detention. In this paper the craftwork is described and the cultural, economic, political and sociological contexts of the industry, as well as its long-term effects, are examined. Comparisons are drawn between the craftwork of the German internees of the First World War and the craftwork done by Boer prisoners during the Anglo-Boer War. A catalogue, in English translation, of the works marketed by the Kamp-industrie organisation is included as the first published record of this remarkable cultural endeavour. To cite this paper: Dominy, G. & Reusch, D. 1993. Handicrafts, philanthropy and self-help: the Fort Napier Kamp-Industrie during World War I. Natal Museum Journal of Humanities 5: 207-24.